A ANALISA KOMPONEN ELEKTRONIKA PADA SWITCHING POWER SUPPLY TIPE OSKA DENGAN METODE INSPEKSI VISUAL DAN MENGGUNAKAN MULTIMETER DIGITAL - Pebrian, Reza; Ali Topan, Paris; Ariyanto, Nova; Hidayatullah, Muhammad (Program Studi Teknik Elektro, 2024)
The Electronics Laboratory of the Electrical Engineering Study Program, Sumbawa University of Technology has various kinds of electronic equipment or components which are used as learning materials for practical work, one of which is the Oska type Switching Power Supply which contains various types of basic electronic components which are often used. This research aims to analyze the feasibility of electronic components in the Oska-type Switching Power Supply using the Visual Inspection method which aims to check and determine the physical condition of electronic components that are still suitable for use as well as using a digital multimeter as a tool to test the suitability of the reference values ??for each electronic component as well as determining components whose physical condition is still good or feasible but in testing the component reference values ??do not match. This research succeeded in analyzing electronic components such as resistors which experienced shrinkage of 48%, capacitors of 40%, and Phototransistor sensors on Optocouplers did not work so these components were not suitable for use, while other components such as Diodes, Integrated Circuits, Light Emitting Diodes, Transistors, and High-Frequency Transformers can still be used.